(untitled) (Fiep Bulletin - online, 2011)
The objective of this study was to verify how important are the physical activities offered on the "Jacques da Luz Filho" Park to local population. The research was developed through a half-open questionnaire applied for the population with age between 20 and 50 years and some interviews with employees of the park. The result presents given interesting, such as: the modification of the daily habits of that population; the lack that the offered activities gratuitously make all population; the necessity of leisure in that region; the lack of spaces and activities and the value given to the activities that were developed in the Park, that stops good part of the living ones were the only form of leisure and care with the health. The conclusion is that no structure to attend the necessities of population and to change that is necessary to think again about the public politics of leisure.